The Pathogenesis of Parkinson's Disease: A Complex Interplay Between Astrocytes, Microglia, and T Lymphocytes? - MacMahon Copas, Adina N.; McComish, Sarah F.; Fletcher, Jean M.; Caldwell, Maeve A. (Frontiers in Neurology, 2021)
Parkinson's disease (PD), the second most common neurodegenerative disease, is characterised by the motor symptoms of bradykinesia, rigidity and resting tremor and non-motor symptoms of sleep disturbances, constipation, and depression. Pathological hallmarks include neuroinflammation, degeneration of dopaminergic neurons in the substantia nigra pars compacta, and accumulation of misfolded α-synuclein proteins as intra-cytoplasmic Lewy bodies and neurites. Microglia and astrocytes are essential to maintaining homeostasis within the central nervous system (CNS), including providing protection through the process of gliosis. However, dysregulation of glial cells results in disruption of homeostasis leading to a chronic pro-inflammatory, deleterious environment, implicated in numerous CNS diseases. Recent evidence has demonstrated a role for peripheral immune cells, in particular T lymphocytes in the pathogenesis of PD. These cells infiltrate the CNS, and accumulate in the substantia nigra, where they secrete pro-inflammatory cytokines, stimulate surrounding immune cells, and induce dopaminergic neuronal cell death. Indeed, a greater understanding of the integrated network of communication that exists between glial cells and peripheral immune cells may increase our understanding of disease pathogenesis and hence provide novel therapeutic approaches.